A rare case of adult colocolic intussusception secondary to splenosis. Issue 8 (August 2022) - Tang, Xuemei; Gu, Peng; Lu, Wenming
Intussusception is the invagination of a segment of bowel (intussusceptum) into the lumen of an adjacent segment (intussuscipiens). Adult intussusception is rare and typically asymptomatic, although bowel obstruction can be a predominant symptom, making it difficult to diagnose. Splenosis is an uncommon and benign disease, arising from the self-implantation of splenic tissue elsewhere in the body after splenectomy or splenic trauma. Colocolic intussusception secondary to splenosis is rare. We report a case of colon intussusception with a mass in the intussusception detected by ultrasound. Abdominal ultrasound identified the intussusception location but failed to distinguish its pathological properties. Colonoscopy revealed the exudation of necrotic and fibrous tissue. Surgery was performed because of suspicions of a malignant tumor.